2007
DOI: 10.1093/bja/aem165
|View full text |Cite
|
Sign up to set email alerts
|

Crystalloid infusion rate during fluid resuscitation from acute haemorrhage

Abstract: Bolus crystalloid infusion exceeding 80 ml kg(-1) h(-1) may not increase effectiveness of fluid resuscitation. Crystalloid resuscitation for more than 2 h may be detrimental in view of an excessive net fluid retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…In other words, crystalloid infusion can be regarded as a means of irrigating the whole body. Although a large volume of crystalloid is necessary to resuscitate patients in hemorrhagic shock, the effect is transient and is limited by the effective amount; this has been confi rmed by mathematical simulation [40,41]. The results of this mathematical model almost agree with our clinical experience, as we feel that there is a ceiling effect of crystalloid therapy for hemorrhagic hypotension (Fig.…”
Section: Crystalloid Infusion During Hemorrhagesupporting
confidence: 70%
See 1 more Smart Citation
“…In other words, crystalloid infusion can be regarded as a means of irrigating the whole body. Although a large volume of crystalloid is necessary to resuscitate patients in hemorrhagic shock, the effect is transient and is limited by the effective amount; this has been confi rmed by mathematical simulation [40,41]. The results of this mathematical model almost agree with our clinical experience, as we feel that there is a ceiling effect of crystalloid therapy for hemorrhagic hypotension (Fig.…”
Section: Crystalloid Infusion During Hemorrhagesupporting
confidence: 70%
“…This simulation employs the values of such parameters as vascular permeability and the ratio of lymph drainage from experimental data. Therefore, this simulation seemed to provide a feasible result (for details, refer to published articles [40,42]). Clinical experience in patients with sepsis with intractable hemodynamic instability has allowed us to recognize that maintaining the intravascular BV is hard to achieve, despite loading with large volumes.…”
Section: Crystalloid Infusion During Hemorrhagementioning
confidence: 99%
“…showed that a 75 mL/kg crystalloid infusion after hemorrhage momentarily restored BV during the infusion. When the infusion was stopped, however, BV decreased rapidly to a volume lower than it had been before the infusion [75]. This finding supports a concept developed using homeostatic blood states theory that a physiologic target BV will change according to changes in red cell volume; for example, a decrease of red cells after hemorrhage decreases the physiologic target BV by the volume of lost red cells [73].…”
Section: Reviewsupporting
confidence: 64%
“…In conclusion, an adaptive C‐L fluid administration system based on a compartmental model of fluid distribution computed an infusion rate to drive an endpoint of resuscitation (eg, SVV) during both absolute (controlled or uncontrolled), relative hypovolemia, or a combination of relative hypovolemia and absolute controlled hypovolemia. Fluid rates and volumes delivered approximated values recommended by studies that have modeled different fluid rates and volumes required to restore and maintain blood volume after acute hemorrhage . The proposed adaptive control framework did not require subject‐specific information (eg, age, gender, weight, diagnosis).…”
Section: Discussionmentioning
confidence: 98%